2019
DOI: 10.1111/1365-2745.13286
|View full text |Cite
|
Sign up to set email alerts
|

Plant physical and chemical traits associated with herbivory in situ and under a warming treatment

Abstract: Plants protect themselves against herbivore attacks with physical traits and toxic secondary metabolites. Levels of plant defences and herbivore performance might shift under climate warming, particularly in alpine habitats, where herbivore pressure is currently low. Plant responses to warming should be driven by species‐specific shifts in physical and chemical defence traits. We investigated the association between plant leaf physical and chemical traits and herbivory under current and warmer climates in thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
50
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 113 publications
2
50
1
Order By: Relevance
“…However, there was substantial variation in thermal responses among individual pairs. Descombes et al 9 found that warming modified physical and chemical phenotypes of all studied plant species. However, the trait changes did not result in a consistent effect on plant resistance against herbivores.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…However, there was substantial variation in thermal responses among individual pairs. Descombes et al 9 found that warming modified physical and chemical phenotypes of all studied plant species. However, the trait changes did not result in a consistent effect on plant resistance against herbivores.…”
mentioning
confidence: 98%
“…Higher temperatures are predicted to increase population densities of most insect species and cause alterations in their body size, life cycle duration and in the extent of their host plant exploitation 7 strengthening the intensity of the plant-herbivore interactions (e.g., 7,8 ). However, other studies showed that warming can reduce plant-herbivore interactions in some systems, and the responses thus seem to be species specific 5,6,9,10 . A possible explanation for this specificity is the differential effects of temperature on plant traits that determine plant palatability.…”
mentioning
confidence: 99%
See 3 more Smart Citations